SISTEM PENGELOLAAN DAN PELAYANAN TERHADAP KEPUASAN PEDAGANG DI PASAR SENTRAL RAPPANG KABUPATEN SIDENRENG RAPPANG - Adam Latif; Samsul Samsul (Jurnal Bisnis dan Kewirausahaan, 2017)
The main study in this research is the management system and service to the satisfaction of traders in Rappang Central Market of Sidenreng Regency. The research was conducted with the aim to know the management system and service to the satisfaction of merchant in Pasar Sentral Rappang. The type of research used is descriptive quantitative with data collection method that is survey research method through instrument instrument such as, observation, questionnaire and documentation, with respondents ie traders remain in the central market. Data analysis technique used data analysis using five likert scale which have been modified by the writer. The result of research shows the variable of management of central market management system of Rappang of Sidenreng Rappang Regency with the result of "less good" research. Evident from through management indicators; 1) arrangement of selling places that do not have kiosks, stalls, with percentage of 55.2% criteria "less good", 2) arrangement of grouping / territorial based on kinds and types of merchandise is still not good with percentage only 60.4%, 3) parking area, parking area is still not good with the percentage is only 57.6%, 4) policy formulation and the involvement of traders in the formulation of policy is still quite unfavorable with only 53.4% ​​percentage; 5) supervision by the Head of Market is less good with percentage only 58.51%. Variable service by Central Market Rappang managers measured through 10 indicators, only indicator "responsibility" still not good with percentage only equal to 60,60%, indicator "completeness of facilities and infrastructure" also still less good or less complete with only percentage 57 , 91%.